TKD training program developed for young children aged 10-14 years in Iceland and its necessary evaluations tools - Meisam Rafiei 1986- (2019)
The current Bachelor Science (BS) project, at the department of Sports Science is about a TKD training program for children aged 10-14 years old in Iceland. Although there are many TKD training clubs, each club has their own training program with a different focus. Particularly, current TKD training in most clubs in Iceland is lacking information on how to structure particular skills and fitness training combinations for young and promising children in TKD. In this program there is a constructed program for a proper TKD training adapted with worldwide TKD coaching knowledge for young children to greatly improve the quality of the future TKD athletes in Iceland. The program is ment to be a guide for coaches and athletes who intend to study taekwondo furter and improve theire skills and knowledge in the sport. The sport is growing fast in Iceland and any new programs can help to develop it even further. Fitness and sparring performances are in constant development.